A Lewis acid-promoted Pinner reaction - Pfaff, Dominik; Nemecek, Gregor; Podlech, Joachim (Beilstein Journal of Organic Chemistry, 2013)
Carbonitriles and alcohols react in a Lewis acid-promoted Pinner reaction to carboxylic esters. Best results are obtained with two equivalents of trimethylsilyl triflate as Lewis acid. Good yields are achieved with primary alcohols and aliphatic or benzylic carbonitriles, but the straightforward synthesis of acrylates and benzoates starting with acrylonitrile and benzonitrile, respectively, is similarly possible. Phenols are not acylated under these reaction conditions. The method has been used for the first total synthesis of the natural product monaspilosin. In the reaction of benzyl alcohols variable amounts of amides are formed in a Ritter-type side reaction.
Keywords: carbonitriles; carboxylic esters; Lewis acids; Pinner reaction; Ritter reaction